A comparison of self-reported teaching practices focused on student skills in introductory geoscience courses at two-year and four-year institutions: Results from the National Geoscience Faculty Survey. Issue 4 (2nd October 2021) - Gamage, Kusali; McFadden, Rory R.; Heather Macdonald, R.
Abstract: Community colleges are a major entry point for many students to post-secondary education, particularly for minority, first-generation, low-income, and older students. A range of factors including transfer-readiness, curricular alignment, financial barriers, and transfer guidance, influence successful transfer between two-year colleges (2YCs) and four-year colleges and universities (4YCs). One critical factor related to transfer-readiness may be the degree to which students have similar experiences in the development of key skills in their introductory courses. This study uses the 2016 National Geoscience Faculty Survey to compare self-reported teaching practices used by instructors in introductory geoscience courses that support the development of students' quantitative, data analysis, problem-based, communication, and metacognitive skills in 2YCs and 4YCs. Based on responses of 1, 027 instructors (238 in 2YCs and 789 in 4YCs), a majority of the teaching practices in skills development in 2YCs are similar to those in 4YCs. Of the 24 teaching practices analyzed, seven displayed statistically significant differences after accounting for class size and active class time, however, the logistic models do not predict major differences between 2YCs and 4YCs. The findings of this study may serve to initiate discussions and collaborations between 2YCs and 4YCs, which could strengthen the transfer process and reduce challenges for transfer students.